Manufacture and Properties of Non-Wood Binderlessboard: Effect of Storage Method and Manufacturing Process on Chemical Composition of Bagasse Binderlessboard - Ragil Widyorini; Shuichi Kawai (Wood Research Journal, 2010)
Effects of storage and pressing methods on the chemical composition of Sugarcane (Saccharum officinarum L.) bagasse binderlessboards were investigated by chemical and spectroscopic analyses. The inner layer (core/pith) and the outer hard fibrous layer (face/rind) of bagasse were used as raw materials. The result showed that effect of steam-injection pressing was higher than hot pressing treatment on the chemical composition of bagasse binderlessboards. Under steam-pressure of 1.0 MPa for 10 min, hemicelluloses of bagasse were more significantly degraded than α-cellulose and lignin. Decreasing of Syringyl/Guaiacyl (S/G) and Cinnamic acids/Guaiacyl (C/G) ratios indicated that modification of lignin had occurred during steam and heat treatments. Considering that the residual sugar in bagasse was still high, the storage method of Sugarcane bagasse was an important key for producing bagasse binderlessboards.